Integrated Hospital Payment Information System Modeling Analysis Using the Pieces Method - Kabul Putra Imanuel Mone; Kurnia Ekasari; Anik Kusmintarti (Indonesian Journal of Business Analytics, 2023)
The integrated payroll information system modeling is the focus of this work. The Aisyiyah Bojonegoro hospital is the subject of the investigation. This case study underwent analysis in order to identify and then formulate any issues with the topic of the study. This study employs the PIECES analysis technique, which is thoroughly examined, and the results are presented in the form of a business process model based on Business Process Management Notation (BPMN). BPMN can be used to improve business processes in hospital payroll systems as well as increase effectiveness and efficiency.